British naval supremacy and Anglo-American antagonisms, 1914-1930 - Lisio, Donald J. (Cambridge University Press, 2014)
"During World War I, British naval supremacy enabled it to impose economic blockades and interdiction of American neutral shipping. The United States responded by building 'a navy second to none, ' one so powerful that Great Britain could not again successfully challenge America's vital economic interests. This book reveals that when the United States offered to substitute naval equality for its emerging naval supremacy, the British, nonetheless, used the resulting two major international arms-control conferences of the 1920s to ensure its continued naval dominance"--